2002
DOI: 10.1111/1467-8624.00501
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Mind–Mindedness and Attachment Security as Predictors of Theory of Mind Understanding

Abstract: This study investigated relations between social interaction during infancy and children's subsequent theory of mind (ToM). Infant-mother pairs (N = 57) were observed in a free-play context at 6 months. Interactions were coded for (a) mothers' use of mental state language that commented appropriately on the infants' mental states, and (b) mothers' use of mental state language that did not appropriately reflect their infants' minds. A third variable was (c) security of attachment, which was assessed using the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

49
514
6
31

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 606 publications
(600 citation statements)
references
References 34 publications
49
514
6
31
Order By: Relevance
“…Meins's explanation for the connection between attachment security and social cognitive development is that the same parental characteristic that results in secure attachment also results in the "exposure of the infant to mental state language" (p. 337). She found that maternal child-centered (mindminded) language (but not mindminded language about other people) to 6-month-olds predicted children's false belief performance at age 4 (Meins et al 2002). This evidence requires an explanation of how exposure to mental state language influences social development, which is what we have provided here.…”
supporting
confidence: 57%
See 3 more Smart Citations
“…Meins's explanation for the connection between attachment security and social cognitive development is that the same parental characteristic that results in secure attachment also results in the "exposure of the infant to mental state language" (p. 337). She found that maternal child-centered (mindminded) language (but not mindminded language about other people) to 6-month-olds predicted children's false belief performance at age 4 (Meins et al 2002). This evidence requires an explanation of how exposure to mental state language influences social development, which is what we have provided here.…”
supporting
confidence: 57%
“…In order for children to benefit most from social interaction in constructing a ToM, the interlocutor should be sensitive to and cognisant of the child's current state of mind. For example, in one of our longitudinal studies on the social determinants of ToM performance, we found that mothers' use of mental state language that commented appropriately on their 6-month-olds' putative mental states was an independent predictor of children's ToM performance at age 4 (Meins et al 2002). In contrast, indices of the general quality of the mother-infant relationship (maternal sensitivity and attachment security) did not predict children's subsequent ToM.…”
mentioning
confidence: 73%
See 2 more Smart Citations
“…Mind-mindedness is associated with a range of positive child outcomes. Higher levels of caregiver mind-mindedness in the first year of life are known to predict secure caregiver-child attachment (Arnott & Meins, 2007;Lundy, 2003;Meins et al, 2001; and superior performance on theory of mind tasks at ages 2 (Laranjo, Bernier, Meins, & Carlson, 2010) and 4 (Meins et al, 2002(Meins et al, , 2003). But mind-mindedness is unrelated to children's temperament (Meins, Fernyhough, Arnott, Turner, & Leekam, 2011) and general cognitive ability (e.g., Meins et al, 2001), suggesting that individual infant characteristics do not determine caregivers' mind-mindedness.…”
mentioning
confidence: 99%